Disseminated penicilliosis (non-Penicillium marneffei) in an immuno-competent individual in Malaysia. (June 2018) - Zainudin, Lily Diana; Raja Shariff, Raja Ezman Faridz; Hanafiah, Mohammad; Mohd Noh, Rosnida; Yuhana, Yazzli; Awad, Siti Norbahiyah
Penicilliosis infection caused by Penicillium marneffei is the third most common opportunistic infection in Human Immunodeficiency Virus patients in South-east Asia; however, Penicillium infection caused by non- P. marneffei is uncommon. We present a case of an immunocompetent male with disseminated penicilliosis (non- P. marneffei ) presenting with recurrent empyema. The case described illustrates the challenges in managing a complicated systemic infection and the outcomes of a delayed presentation, in a potentially treatable disease.